A martingale representation for matching estimators - Alberto Abadie; Guido W. Imbens (Institute for the Study of Labor (IZA), 2009)
Matching estimators are widely used in statistical data analysis. However, the distribution of matching estimators has been derived only for particular cases (Abadie and Imbens, 2006). This article establishes a martingale representation for matching estimators. This representation allows the use of martingale limit theorems to derive the asymptotic distribution of matching estimators. As an illustration of the applicability of the theory, we derive the asymptotic distribution of a matching estimator when matching is carried out without replacement, a result previously unavailable in the literature.
urn:nbn:de:101:1-2009033061
Keywords: C13; C14; C21; 330; Matching; martingales; treatment effects; hot-deck imputation; Statistische Methode; Matching; Schätztheorie; Martingale; Theorie